Alexandrite spectroscopic and laser characteristic investigation within a 78–400 K temperature range. (31st October 2017) - Fibrich, M; Šulc, J; Vyhlídal, D; Jelínková, H; Čech, M
Abstract: We report on the influence of temperature on the spectroscopic and lasing properties of alexandrite ( C r 3 + : B e A l 2 O 4 ) crystal. The fluorescence lifetime, polarization-resolved absorption and emission spectra, and laser characteristics at  ̃750 nm are described in detail within a 78–400 K temperature range. As a pumping source, a 3.5 W InGaN blue laser-diode operating at a wavelength of 444 nm was used. The best results achieved were at a crystal temperature of  ̃353 K with 326 mW of continuous output power at a wavelength of 750 nm with a slope efficiency near 20% (related to absorbed pump power). At cryogenic temperatures, alexandrite laser generation at the so-called R-line, i.e. not in the vibronic mode, has been observed.